2004
DOI: 10.1111/j.0019-8676.2004.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of the Boston Living Wage Ordinance*

Abstract: This paper presents one of the first quantitative assessments of the effect living wage laws have had on firms covered by their mandate. Applying difference‐in‐difference estimation methods to survey data from Boston, Massachusetts, I find little evidence of reduced employment or hours worked, following living wage implementation. Instead, there is strong evidence that firms actually shifted from part‐time towards full‐time staffing as a result of Boston's living wage law. Estimates also reveal a substantial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Obviously, therefore, CPS data are not useful in exploring the microeconomic effects of living wages at the firm or establishment leveli.e., questions such as whether firms engage in substitution away from low-wage labor, how much wages are increased for their lowest-wage workers, how employment responds, whether turnover falls, etc. Such questions are best addressed using direct survey data on covered employers (and ideally a control group of uncovered or unaffected employers), as has begun to occur in some recent research (e.g., Brenner, 2003;Fairris, 2003). On the other hand, the CPS data are very useful (and perhaps the best data available at present) for addressing policy questions regarding the effects of living wages on low-wage workers and low-income families, because they permit us to estimate the net effects (including indirect or perhaps "general equilibrium" effects) of living wage laws on workers and families in the cities where they are passed, relative to other cities.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, therefore, CPS data are not useful in exploring the microeconomic effects of living wages at the firm or establishment leveli.e., questions such as whether firms engage in substitution away from low-wage labor, how much wages are increased for their lowest-wage workers, how employment responds, whether turnover falls, etc. Such questions are best addressed using direct survey data on covered employers (and ideally a control group of uncovered or unaffected employers), as has begun to occur in some recent research (e.g., Brenner, 2003;Fairris, 2003). On the other hand, the CPS data are very useful (and perhaps the best data available at present) for addressing policy questions regarding the effects of living wages on low-wage workers and low-income families, because they permit us to estimate the net effects (including indirect or perhaps "general equilibrium" effects) of living wage laws on workers and families in the cities where they are passed, relative to other cities.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers in this area are likely to remain dependent on cross-city comparisons, because observational evidence from comparisons of covered and noncovered firms or individuals within living wage cities is still rare, and appropriate control groups are often difficult to identify (Reich, Hall, and Jacobs 2005;Pollin 2005;Brenner 2005;Fairris 2005;Reynolds and Vortkamp 2005). Without better knowledge about the conditions under which cities pass living wage laws, then, many of our inferences about their effects may be biased (Reich 2003).…”
mentioning
confidence: 99%
“…Studying the impact of a living wage ordinance that impacted workers at the San Francisco International Airport, Reich et al (2005) find that the ordinance increased the wages of low-wage workers, with no evidence of adverse employment effects. Similarly, Brenner (2005) finds that the living wage ordinance in Boston did not reduce employment or hours worked, yet this ordinance applied only to public contractors, where Neumark et al (2012) also found evidence of smaller employment impacts. Finally, Fairris (2005) studies the effect of Los Angeles' living wage ordinance, and finds that Minimum Wages and Human Capital Acquisition.…”
Section: Local Minimum Wages and Living Wage Ordinances While Most Smentioning
confidence: 99%
“…Neumark and Adams (2005a) suggest the larger bite of living wage laws which cover businesses who receive financial assistance may be explained by higher concentrations of living wage laws in contiguous or nearby labor markets for cities which also cover business assistance recipients. 13 A handful of studies have taken the case study approach to estimate the wage and employment effects of living wage ordinances (Brenner 2005;Fairris 2005;Reich et al 2005). Studying the impact of a living wage ordinance that impacted workers at the San Francisco International Airport, Reich et al (2005) find that the ordinance increased the wages of low-wage workers, with no evidence of adverse employment effects.…”
Section: Local Minimum Wages and Living Wage Ordinances While Most Smentioning
confidence: 99%